Usage of air-conditioners and windows in residential areas in Johor Bahru City : planning methods of coastal residential areas in consideration of wind flow - Tetsu, Kubota (2006)
This study discusses planning methods of residential areas in coastal cities, focusing on the effect of wind flow. This aims to determine strategies that reduce energy consumption in residential areas, targeting especially a reduction in the use of air-conditioners. As a part of the above study, this paper presents the findings of a questionnaire survey on usage of windows and air-conditioners among selected households in apartment houses in Johor Bahru City, Malaysia and compares the results with those in terraced houses surveyed previously.